A thematic analysis of examiners’ questions in master’s students’ thesis oral examination - Widyantoro, Agus; Mukminatun, Siti; Nurharjanto, Asfar Arif; Permatasari, Indah (Indonesian Journal of Applied Linguistics, 2024)
Oral examinations in higher education context have been an under-explored genre in academic discourse since it is not easily accessible for public, rendering a complexity in understanding examiners’ expectations during the exam. Having adequate repertoire of the examiners’ questions among the students being assessed can lead to successful oral defense without exception among Master’s students. Hence, this research aims to explore the typical questions asked by the examiners during Master’s students’ thesis oral examination. Seventeen recorded oral examination videos involving four examiners in the Indonesian higher education context were collected with the consent from the participants involved in the videos. They were transcribed and analyzed using a thematic analysis approach to explore the types of examiners’ questions. The findings demonstrate that there were five main categories of questions typically posed by the examiners in order from the most frequently appeared to the least one: (1) questions clarifying specific points in the thesis report or presentation, (2) questions related to the linkage between research method and findings, (3) questions related to the review of literature, (4) general preliminary questions, and (5) questions regarding the process of recruiting or selecting research participants. Questions revealed in each category also represent a particular purpose during the examination process. The results can be used as a reference for graduate students in preparing their oral defense.